Penggunaan Website Sipmen Pada Penilaian Kinerja Pegawai Badan Pusat Statistik Kabupaten Karawang - Aditya Wisnu Ardhana; Uus Muhammad Darul Fadli (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
In a predetermined target, it is necessary to set an assessment as a form of attention to the performance of employees because at the same time employees need the assessment as feedback. Employee performance can be achieved by groups or individuals in a company qualitatively or quantitatively. Because of the evidence that shows that the use of the document management information system (SIPMEN) website also has a significant role in employee performance by managing all employee data and evaluating the performance of employees of the Central Bureau of Statistics Karawang Regency which is systematized and very effective to record employee performance at BPS Karawang so as not to spend much time in processing Employee Performance Achievements. This research uses qualitative methods. This research was conducted at the Office of the Central Bureau of Statistics Karawang Regency, on Jl. Cakradireja No.36, Nagasari, West Karawang, Karawang, West Java. The data sources used are primary data sources through interviews with predetermined informants. The data analysis technique used in this study is interactive analysis. The discussion of performance appraisal on work results and attendance has a coverage of up to 90% (sufficient) because of several obstacles faced, if you look at other indicators, it has a performance level of 100% (Good). This is due to the availability and completeness that has facilitated the implementation of the process. The conclusion of this study is that the author gained new knowledge and insights regarding performance appraisal in employees of the Central Bureau of Statistics Karawang. The author can also find out the performance appraisal process to evaluate work performance both internally and externally. There are several suggestions such as speeding up the evaluation of constraints.